Transforming Microfinance Institutions : Providing Full Financial Services to the Poor. - Ledgerwood, Joanna (Online access: World Bank World Bank Open Knowledge Repository., 2006)
In response to a clear need by low-income people to gain access to the full range of financial services including savings, a growing number of microfinance NGOs are seeking guidelines to transform from credit-focused microfinance organizations to regulated deposit-taking financial intermediaries. In response to this trend, this book presents a practical 'how-to"" manual for MFIs to develop the capacity to become licensed and regulated to mobilize deposits from the public. ""Transforming Microfinance Institutions"" provides guidelines for regulators to license and regulate microfinance provider.